2006 2nd International Conference on Information &Amp; Communication Technologies
DOI: 10.1109/ictta.2006.1684384
|View full text |Cite
|
Sign up to set email alerts
|

Digital Libraries: From Process Modelling to Grid-based Service Oriented Architecture

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…It was found that the business process modelling using RAD proved to be useful in visualizing the periodicals’ acquisitions process in academic libraries and reveal further process improvements (such as finding out communication problems and removing unnecessary tasks). Khan et al (2006) investigated the process of a scientific publishing process for digital libraries using RAD. Green et al (2013) applied Riva to two higher education institutions, to create process architectures using the PAD.…”
Section: Business Process Modelling In Academic Librariesmentioning
confidence: 99%
“…It was found that the business process modelling using RAD proved to be useful in visualizing the periodicals’ acquisitions process in academic libraries and reveal further process improvements (such as finding out communication problems and removing unnecessary tasks). Khan et al (2006) investigated the process of a scientific publishing process for digital libraries using RAD. Green et al (2013) applied Riva to two higher education institutions, to create process architectures using the PAD.…”
Section: Business Process Modelling In Academic Librariesmentioning
confidence: 99%
“…In another work, Khan et al (2006) investigated the process of a scientific publishing process for digital libraries. The process was modelled using RAD.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Modelling that process was part of understanding the system's requirements which could therefore be used to enhance the legacy system or integrate it with other parts of the information system. Khan et al (2006) investigated the process of a scientific publishing process for digital libraries.…”
mentioning
confidence: 99%